AgX@carbon (X = Br and I) as robust and efficient catalysts for the reaction of propargylic alcohols and CO2 to carbonates under ambient conditions. Issue 59 (3rd June 2016) - Qiu, Jikuan; Zhao, Yuling; Wang, Huiyong; Cui, Guokai; Wang, Jianji
Abstract : An easily prepared AgX@C material was found to be a highly efficient catalyst for transforming CO2 into carbonates. Abstract : Development of new efficient catalytic systems for chemical transformation of CO2 is a very attractive topic in green chemistry. In this work, we studied the synthesis of α-alkylidene cyclic carbonates through the coupling reaction between propargylic alcohols and CO2 with new silver catalysts. It was found that activated carbon supported AgX (X = Br and I) was a simple and efficient catalyst for the carboxylative cyclization of propargyl alcohols with CO2 at atmospheric pressure and room temperature. Nearly 99% yield of the desired product was obtained, and the product could be simply separated through solvent extraction. Moreover, the catalyst could be easily recovered and reused at least ten times without a decrease in the catalytic activity and selectivity. These findings are useful for the development of an environmentally friendly chemical process for the production of α-alkylidene cyclic carbonates.